Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1046/j.1365-4362.1997.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatography with bleomycin as a new treatment for verrucae vulgaris

Abstract: Dermatography proved to be an effective technique for intralesional administration of bleomycin in more than two-thirds of patients resistant to conventional therapy. Treatment failures in this study could in part be explained by a defective immune system in the patients. Dermatography is a technique that can be learned by any skillful dermatologist or plastic surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…Thus, their average duration approaches the mean duration of spontaneous cure. The clearance rate of 87.88% achieved in the present study is similar to that of previous reports using bleomycin [3,4,6,7,8,9,10]. While the pharmacological mechanism of pingyangmycin for wart treatment remains to be revealed, we assume that it has clinical effects similar to bleomycin as pingyangmycin is a member of the bleomycin reagent family [11].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, their average duration approaches the mean duration of spontaneous cure. The clearance rate of 87.88% achieved in the present study is similar to that of previous reports using bleomycin [3,4,6,7,8,9,10]. While the pharmacological mechanism of pingyangmycin for wart treatment remains to be revealed, we assume that it has clinical effects similar to bleomycin as pingyangmycin is a member of the bleomycin reagent family [11].…”
Section: Discussionsupporting
confidence: 90%
“…Open studies have suggested clearance rates of approximately 20-90% of treated warts with one or more treatments, 101,102 with most reporting a patient response rate of approximately 65-85%. 101,103 Several trials of intralesional bleomycin have used saline as a placebo. In one study where 25 patients were allocated to each treatment, 96% (82/85) of warts treated with bleomycin cleared, while only 11% of warts (eight of 72) treated with saline showed clearance at 3 months.…”
mentioning
confidence: 99%
“…Micropigmentation was also used recently for nipple‐areola reconstruction, enhancement of eyebrows and eyelashes, permanent repigmentation of achromic burn scars, reconstitution of eyebrows following recalcitrant alopecia areata, and esthetic improvements of scars and skin grafts, especially to camouflage hairless patches 19–23 . It is a useful adjunctive therapy for camouflaging disturbing discolorations and scars of the head and neck, reports of which have included color matching of vermilionplasty after radial forearm free flap reconstruction of the lower lip, cleft lip and cleft palate scars, senile lip rejuvenation, and an alternative treatment for disturbing corneal scars 24–29 …”
Section: Indications Of Micropigmentationmentioning
confidence: 99%
“…[19][20][21][22][23] It is a useful adjunctive therapy for camouflaging disturbing discolorations and scars of the head and neck, reports of which have included color matching of vermilionplasty after radial forearm free flap reconstruction of the lower lip, cleft lip and cleft palate scars, senile lip rejuvenation, and an alternative treatment for disturbing corneal scars. [24][25][26][27][28][29]…”
Section: Indications Of Micropigmentationmentioning
confidence: 99%